A novel technique to model water uptake by plants in geotechnical centrifuge. Issue 4 (29th September 2014) - Ng, C. W. W.; Yu, R.
Abstract : Although geotechnical centrifuge modelling of vegetated slopes has become increasingly popular, attention has been mainly focused on modelling the mechanical effect of roots. The hydrological effect, namely, water uptake and thus induced negative pore-water pressure (PWP), has attracted relatively less attention. Negative PWP (i.e., suction) increases soil shear strength but decreases hydraulic conductivity, both of which help enhance slope stability. This letter introduces a novel technique developed for modelling plant water uptake in geotechnical centrifuge. The technique involves using a branch cutting to model the plant root to which vacuum is delivered to generate a pressure gradient. This enables water to be extracted from the soil into the branch cutting and thus a negative PWP to be induced in the surrounding soil. The effectiveness of this technique was evaluated by testing a model slope 'vegetated' with 45 pieces of branch cuttings in the centrifuge. Measurements show that negative PWP can be induced under 20 g condition and the PWP distribution is reasonably consistent with field data. This technique makes it possible to investigate the effects of negative PWP induced by vegetation water uptake on slope deformation and stability using the geotechnical centrifuge.